the guidence for knowledge and competence in oral hygiene care at Balingbing and Cidadap Village, Subang West Java. - Hidayat, Wahyu (Universitas Padjadjaran, 2017)
AbstractIndonesian development can not be separated from the public health development. The improvement of community oral health status is currently focused on promotive and preventive, with the goal to make good health care as a positive habit in the society. Currently the spread of medical and health facilities in Indonesia is still not well distributed and the amount is less than the population. The government also concerned to establish a health care cadre to helps the promotion and prevention activity in the community. So it is necessary to set up dental health cadre as part of general health care. The goals of this KKNM PPMD programme is to create some volunteers for dental health care, including dental students, cadres of PKK and Posyandu, and elementary school children. This programme also provide some social service in order to know the oral health condition in target population. Approximately less than 30 âPKKâ and âposyanduâ cadres got topics about oral health maintanance given by dental students under supervision of lecturers. From oral examination showed coated tongue as most common oral lesion with the number of 76 children.The success of making cadres based on the good results of the pretest and post test. This cadres are expected can transfer knowledge toÂ improve the quality of life in community.Keywords : Oral health, cadre, oral lesion